á¸¤ukm IdnÄ' al-JilbÄb: Dirasah an-Niáº“Äm al-IjtimÄ'Ä« fÄ« Naáº“or Naqdi al-á¸¤adÄ«th wa Ä€yÄt al-Aá¸¥kÄm - Imamul Arifin; Dianidza Arodha; Meriyati; Sukataman; Choliliyah Thoha (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2026)
This study examines the concept of lowering the jilbab in Islamic jurisprudence (fiqh) through an integrative approach that combines a textual study of the Qur’an and the Prophetic Hadith with a socio-religious analysis of contemporary practice. The study takes as its starting point the Qur’anic verse in Sūrah al-Ahzāb (59) as the legislative basis for the command to let the jilbāb hang down, then focuses on the relevant hadith, tracing its transmission, examining its chain of transmission, and comparing it with the accounts found in the exegesis. It provides a practical description of how the women of the Ansar complied with the command to let the jilbab hang down, as recorded in the reasons for revelation. The research adopts a qualitative methodology by combining desk-based and field research, analysing the views of exegetes and jurists on the meaning of the jilbab and ‘idna’, and conducting field observations and in-depth interviews with Muslim women from diverse social and educational backgrounds. The findings reveal that the motivations for wearing the long jilbab vary, including religious commitment, the construction of social identity, the influence of fashion and social media, and family and cultural factors. The research also highlights a significant jurisprudential difference regarding the issue of face covering, whereby ‘idna’ is not understood as an absolute obligation to cover the face but is linked to the objectives of Sharia, such as covering the ‘awrah’, preventing fitnah, and preserving dignity.